1997
DOI: 10.1093/ajcp/107.4.410
|View full text |Cite
|
Sign up to set email alerts
|

Useful Panel of Antibodies for the Classification of Acute Leukemia by lmmunohistochemical Methods in Bone Marrow Trephine Biopsy Specimens

Abstract: To evaluate the feasibility of acute leukemia typing on routinely processed bone marrow biopsy specimens, 72 cases of previously established acute leukemia covering the spectrum of 17 known subtypes were studied immunohistochemically. Most leukemic myeloblasts were positive for myeloperoxidase in 16 (84%) of 19 cases of acute myeloid leukemia, M1-M4, and M6. Most leukemic cells in 11 of 12 M4 and M5 cases were positive for CD68 (PG-M1). All six M6 cases stained with hemoglobin. Leukemic megakaryoblasts in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 29 publications
(16 reference statements)
2
16
0
2
Order By: Relevance
“…Since CD61 reacts poorly in B5-fixed and/or nitric acid decalcified bone marrow biopsies, vWF has usually been the antibody of choice, at least in the United States. 37,40 However, published evidence has shown that vWF expression is frequently decreased in cases of AMKL with poorly differentiated blasts, 6 a finding consistent with the decreased synthesis of alpha granules (where vWF is stored) in immature megakaryocytes.…”
Section: Acute Panmyelosis With Myelofibrosismentioning
confidence: 88%
See 1 more Smart Citation
“…Since CD61 reacts poorly in B5-fixed and/or nitric acid decalcified bone marrow biopsies, vWF has usually been the antibody of choice, at least in the United States. 37,40 However, published evidence has shown that vWF expression is frequently decreased in cases of AMKL with poorly differentiated blasts, 6 a finding consistent with the decreased synthesis of alpha granules (where vWF is stored) in immature megakaryocytes.…”
Section: Acute Panmyelosis With Myelofibrosismentioning
confidence: 88%
“…[32][33][34][35] The identification of megakaryoblasts and atypical megakaryocytic forms can be greatly facilitated by the use of monoclonal antibodies reactive with platelet glycoproteins, such as CD41 (glycoprotein IIb/IIIa), CD42 (glycoprotein Ib), or CD61 (glycoprotein IIIa), or with a polyclonal antifactor VIII (vWF) antibody. [36][37][38][39] However, of the three antiplatelet glycoprotein antibodies, only CD42 and CD61 are demonstrable in routinely processed tissue sections. Since CD61 reacts poorly in B5-fixed and/or nitric acid decalcified bone marrow biopsies, vWF has usually been the antibody of choice, at least in the United States.…”
Section: Acute Panmyelosis With Myelofibrosismentioning
confidence: 99%
“…But in some cases, the ability to immunophenotype acute leukemias by these methods is markedly limited when blast cells are not present in the peripheral blood sample and when no bone marrow can be aspirated, for example, because of bone marrow fibrosis. In these cases MAb 56C6 should be H e m a t o p a t h o l o g y / ORIGINAL ARTICLE useful as part of a panel of paraffin-reactive antibodies against myeloperoxidase, CD68 (clone PGM-1), TdT, CD79a, and CD3 to differentiate AMLs from precursor B-ALLs, 8,9 as CD 10 usually is detectable in the latter, whereas CD 10 expression in AMLs is an exceptionally rare event. 3 However, for evaluating paraffin-embedded bone marrow biopsy specimens for primary or relapsing infiltrates of B-lineage ALLs using MAb 56C6, it is essential not to mistake nonneoplastic immature B-lineage lymphoid precursors expressing CD 10 (socalled hematogones) for neoplastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Myeloperoxidase is the most specific marker for assigning myeloid lineage ( Figure 7b); however, is negative in AML-M0 and blasts of monocytic, erythroid, and megakaryocytic lineages. Hemoglobin A1 and glycophorin A are positive in 90% to 100% of erythroid lineage cells, and FVIII is positive in 90% of megakaryocytic cells, but rare cases demonstrating inadequate lineage maturation (early megakaryoblasts) may be negative (Chuang SS & Li CY, 1997;Manaloor EJ, 2000 However, it is a challenge to interpret MPO negative AL cases. In such cases of AL, one has to first ensure that the B-and T-lymphoblastic lineages have been ruled out by a negative staining for CD79a, PAX-5, CD20, and CD3 (should detect CD3 epsilon chain and not zeta chain by a polyclonal antibody, which is non-specific) (Swerdlow SH et al, 2008).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%